Pathogenetic interaction of arterial hypertension and insulin resistance - O. N. Korneeva; O. M. Drapkina (Российский кардиологический журнал, 2006)
Metabolic syndrome, or insulin resistance (IR) syndrome, including abdominal obesity (АО), atherogenic dyslipidemy, arterial hypertension (AH), Type 2 diabetes mellitus, DM (or impaired glucose tolerance) etc., is a major cardiovascular threat. Cardiovascular disease remains on the first place in mortality and morbidity structure in economically developed countries. IR and resulting compensatory hyperinsulinemia, are pathogenetically linked to AH development in DM and АО. Modern data on pathogenetic interaction between AG and IR, renin-angiotensin-aldosterone system (RAAS) role in AH and IR development, RASS inhibitor (in particular, ACE inhibitor lisinopril) benefits are presented in the article.